PROSPECTIVE, RELEVANCE AND QUALITY OF HIGHER EDUCATION - Carrión M., Rolando (2003)
This article deals with the obligation of the University to offer an education of quality, framed in the relevancy of its social responsibility by means of the vision of future scenarios as a result of a permanent prospective work.